A novel sequential heap leach process for treating crushed Platreef ore - Mwase, James; Petersen, Jochen; Eksteen, Jacques (Elsevier Science BV, 2014)
A novel sequential heap leaching process has been identified as a possible alternative to the conventional concentrate–smelt–refine route for processing Platreef ore, a platinum group metals containing ore with palladium predominance. The present study focuses on testing this process on crushed whole ore, after initial experiments conducted on low-grade Platreef flotation concentrate achieved promising results. Two samples of drill core Platreef ore with size distributions of - 25 mm + 1 mm and - 6 mm + 1 mm were first bioleached in cylindrical columns, to simulate heap leaching, at 65 °C and then leached with cyanide solution at 50 °C in cylindrical columns. Overall the best results were achieved from the tests on the - 6 mm + 1 mm size fraction sample. After 304 days 93% Cu, 75% Ni and 53% Co were extracted in the bioleach experiment, and after 60 days 57.8% Pt, 99.7% Pd and 90.3% Au in the follow-up cyanide leach experiment. Analysis using a mineral liberation analyser suggested that Pt and Pd were leached mostly from the tellurides while the Pt arsenides appeared resistant to cyanide leaching. From the results it is proposed that the process considered herein is a potential alternative route to treat Platreef ore.